Performance investigation and evaluation of a new three-piston pump energy recovery device for small scale desalination system. (15th May 2022) - Song, Daiwang; Zhang, Yin; Wang, Haitao; Li, Xue; Xiao, Yexiang; Wang, Chengpeng; Wang, Shenghui; Zhang, Qihui; Hu, Jie
Highlights: A new three-piston pump energy recovery device is introduced and evaluated. The flow characteristics in operation are investigated via the numerical method. The efficiency is as high as 82.03% from the experimental desalination testing. The energy consumption of 3.62 kW·h/m 3 is achieved for the desalination system. Abstract: Energy recovery device is a crucial part for decreasing the energy consumption of membrane desalination system. To meet the energy conservation requirements in small scale desalination system, a new three-piston pump energy recovery device integrating the high pressure pump and booster pump is investigated and evaluated. The flow characteristics in pressure exchanging cylinders are investigated through the numerical method. The operating performance is experimentally evaluated in a membrane desalination system at the seawater pressure and flowrate of 5.00 MPa and 6.10 m 3 /h. The numerical results indicate that the continuous flow and pressure transition can be realized through the cooperation of three hydraulic pistons in operation. Both the inlet and outlet flowrates demonstrate the half-sine variation trends. The maximum deviation between simulation and experiment is 2.70%. The experimental results prove that the device can achieve the stable pressure exchanging, and the pressure and flowrate fluctuation amplitudes are 0.60 MPa and 0.60 m 3 /h. The energy recovery efficiency is as high as 82.03% which contributes to a specific energy consumption of 3.62 kW · h / m 3 in desalination. This paper provides a new type of multi-functional energy recovery device for the membrane desalination system.